LECTINS IN ANTI-CANCER STRATEGIES - M. V. Lakhtin; V. M. Lakhtin; V. A. Aleshkin; M. S. Afanasiev; S. S. Afanasiev (Acta Biomedica Scientifica)
The published during last few years data concerning communicative role of lectins (proteins and their complexes which recognize  carbohydrates, glycoconjugates and their patterns) in on-duty  supporting and increasing anticancer status of human immunity are  analyzed. Examples of lectin-(glycoconjugate pattern) strategies,  approaches and tactic variants in study and development of  anticancer treatments, principle variants of therapy, possible  vaccines in 35 cases of blood connected tumors (leukemia,  lymphomas, others), solid tumors (carcinomas, sarcoma, cancers of vaginal biotopes, prostate, bladder, colon, other intestinal  compartments, pancreas, liver, kidneys, others) and cancer cell lines  are described and systemized. The list of mostly used communicative lectins (pattern recognition receptors, their soluble forms, other  soluble lectins possessing specificities of importance) involving in key intercellular cascades and pathway co-functioning is presented. The  regulation of resulting expression of distinct active lectins (available and hetero/di/oligomeric forms) and their interaction to  adequate glycoconjugate patterns as well as influence distribution of  co-functioning lectins and antigens CD between populations and  subpopulations of antigen-presented cells (dendritic cells cDC, mDC,  moDC, pDC; macrophages M2 and M1), mucosal M-cells, NK-cells  play key role for choice and development of anticancer complex  procedures increasing innate and innate-coupled immune responses.  Prospects of (receptor lectin)-dependent intercellular  communications and targeting glycoconjugate constructions into  innate immunity cells for therapy of cancer and development of anticancer vaccines are evaluated and discussed.